2007
DOI: 10.1111/j.1467-9345.2007.00452.x
|View full text |Cite
|
Sign up to set email alerts
|

What do effective teachers of literacy do? Subject knowledge and pedagogical choices for literacy

Abstract: This article explores the fine detail of practice by three teachers, all recognised as effective teachers of literacy. The three were observed during nine literacy lessons (three lessons each), working with Year 2 classes (6/7‐year‐olds) in successful inner‐city primary schools in the south of England. Data collection took place in 2003, just as their schools were moving away from the close early prescription of the National Literacy Strategy (NLS). Follow‐up visits were made in 2005. My initial interest had b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 8 publications
1
22
0
Order By: Relevance
“…The academic program is focused and purposefully well defined with readily apparent goals, lesson plans, long term plans, and assessments (Peterson et al 1991;Farr 2010). These findings are confirmed by research examining the practices of effective elementary teachers in low-income schools who have been successful in helping their students achieve literacy (Lazar 2006;Flynn 2007). Effective teachers implement routines, models, strategies, and carefully constructed approaches to scaffold student learning while also checking for understanding (Lazar 2006;Flynn 2007;Farr 2010).…”
Section: Instructional Practices Of Effective Teachersmentioning
confidence: 51%
See 2 more Smart Citations
“…The academic program is focused and purposefully well defined with readily apparent goals, lesson plans, long term plans, and assessments (Peterson et al 1991;Farr 2010). These findings are confirmed by research examining the practices of effective elementary teachers in low-income schools who have been successful in helping their students achieve literacy (Lazar 2006;Flynn 2007). Effective teachers implement routines, models, strategies, and carefully constructed approaches to scaffold student learning while also checking for understanding (Lazar 2006;Flynn 2007;Farr 2010).…”
Section: Instructional Practices Of Effective Teachersmentioning
confidence: 51%
“…These findings are confirmed by research examining the practices of effective elementary teachers in low-income schools who have been successful in helping their students achieve literacy (Lazar 2006;Flynn 2007). Effective teachers implement routines, models, strategies, and carefully constructed approaches to scaffold student learning while also checking for understanding (Lazar 2006;Flynn 2007;Farr 2010). Effective teachers are constantly preparing for their lessons and working relentlessly (Duncan-Andrade 2007; Farr 2010).…”
Section: Instructional Practices Of Effective Teachersmentioning
confidence: 51%
See 1 more Smart Citation
“…Participants in this study involved in the service learning experience were better able to articulate and support the literacy development of their case study students. Thereby, the complex process of teaching reading resides in the subject knowledge held by teachers and the interactions between the student and teacher, rather than a rigid set of teaching objectives (Flynn, 2007). Furthermore, the preservice teachers in this study demonstrated emerging if not developing characteristics of excellent teachers of reading as defi ned by the IRA (2000).…”
Section: Service Learning In Teacher Preparation Programs: a Worthwhimentioning
confidence: 95%
“…Instead, it is felt that teacher educators should be fostering effective teachers of literacy who critically reflect on their own beliefs regarding literacy, who understand the specific needs of their adolescent students and who use an on-going broad and eclectic collection of methods to develop specialised subject-specific literacy skills (Flynn 2007;Hall and Harding 2003;Harrison 2004;Louden and Rohl 2006). It is through teaching such contextualised subject-specific literacy strategies that specialised subject content would become more meaningful, resulting in deeper learning and understanding of material (Heller and Greenleaf 2007;Kist 2000;Shanahan and Shanahan 2008).…”
Section: A Question Of Teacher Education?mentioning
confidence: 98%